Effect of arterial blood bicarbonate (HCO3 −) concentration on the accuracy of STOP-Bang questionnaire screening for obstructive sleep apnea - Chong Pei (BMC, 2021)
Abstract Background To evaluate the effect of arterial bicarbonate (HCO3 −) concentration on the accuracy of STOP-Bang questionnaire (SBQ) screening for obstructive sleep apnea (OSA). Methods A total of 144 patients with suspected OSA were included. Polysomnograms (PSG) and blood gas analysis were performed, and the Epworth Sleepiness Scale (ESS), STOP-Bang questionnaire, and Berlin questionnaire were completed. The correlation between the arterial HCO3 − concentration, apnea hypopnea index (AHI), and other related indicators was analyzed. The scoring results of the ESS, SBQ, and Berlin questionnaire were compared with the PSG results, and the sensitivity and specificity were calculated in the form of a four-cell table. The changes in the sensitivity and specificity of OSA screening after SBQ alone and combined with HCO3 − concentration were compared, and ROC curves were drawn. Results Arterial HCO3 − concentration was positively correlated with AHI (r = 0.537, P < 0.001). The ratio of HCO3 − concentration ≥ 24.6 mmol/L in the non-OSA group was significantly lower than that in the OSA group (25.0% VS 80.8%, P < 0.001). The sensitivity of the SBQ was higher than that of the ESS (97.5% VS 81.7%, P < 0.001) and the Berlin questionnaire (97.5% VS 79.2%, P < 0.001). There was no statistical significance in the specificity of the three scales (25%, 37.5%, 37.5%). A combined SBQ score ≥ 3 and HCO3 − concentration ≥ 24.6 mmol/L showed increased specificity and decreased sensitivity compared with an SBQ score ≥ 3 alone, with a corresponding AUC of 0.771 (P < 0.01) and 0.613 (P > 0.05), respectively. Conclusion The sensitivity of the SBQ was better than that of the Berlin questionnaire and ESS. After combining arterial blood HCO3 − concentration, the SBQ questionnaire increased the specificity of OSA prediction and decreased the sensitivity, which improved the accuracy of screening.